WATTMETER DIGITAL DENGAN MIKROKONTROLER DAN ARDUINO UNO 2 - Yulian, Eki; Sasmoko, Priyo (Gema Teknologi, 2015)
Eki Yulian, Arkhan Subari in this paper explain that Power consumption in boarding houses still can not be monitored , so that power usage bill payments based solely on electrical equipment used in the room . This would be detrimental to the owner of the boarding when the power consumption is too large . But tenants boarding can also be harmed if rarely use electricity must still pay the electric bill to the owner of the boarding.Thus making the tool use of electricity for the purposes of calculating a dorm room at the end of the project , expected to assist in completing the problem. In this tool using optocoupler sensor mounted on a disc kwh meter analog and microcontroller will process the data readings from sensors optocoupler . The output of this tool will appear on an LCD (liquid circuit display) . Where is the data to be displayed is the amount of power usage and costs to be paid . In addition , the tool uses the SMS facility for monitoring power use. Thus the cost paid by the tenant to the boarding room owner would be more in line with the use of electricity in use by tenants boarding. Keywords :optocoupler sensor, microcontroller , SMSDAFTAR PUSTAKAAndrianto, Heri. 2008. Pemrograman Mikrokontroler AVR ATMEGA 16 Menggunakan Bahasa C (CodeVisionAVR). Informatika: BandungBejo, Agus. 2008. C & AVR.  Graha Ilmu: YogyakartaFidzon, Adil. 2011. Miniatur Sistem Parkir Mobil Otomatis Berbasis Mikrokontroler ATmega8535. Undip : SemarangHardika,  Doni.  2012. Pembuatan Aplikasi Mikrokontroler ATmega8535 Dalam Otomasi Alat Pencacah Permen Skala Home Industri. Undip : SemarangFrank D, Peetruzella. 1996. Elektronika Industri. Andi : YogyakartaMalvino, A.P. 1996. Prinsip-prinsip Elektronika (terjemahan Hanapi Gunawan). Erlangga: JakartaM.C, Sharma. 1993. Praktikal Music dan Sound Circuit. Halaman 123 : New DelhiPratama, LiusWeny. 2009. Sistem Absensi Otomatis Pengunjung Perpustakaan Dengan Menggunakan Radio Frequency Identification. Laporan Tugas Akhir Politeknik Negeri Sriwijaya : PalembangSudjadi. 2005. Teori dan Aplikasi Microcontroller. Graha Ilmu : YogyakartaSumanto, MA. 1984. Mesin Arus Searah. Andi Offset : YogyakartaTurbian, K. 1973. A Manual for Writers of Term Papers, Theses and Dissertations. 4th. Ed. The University of Chicago Press. Chicago.Wardana, E.K. 2013. Pintu Pengaman Untuk Ruang Penyimpanan Dokumen Menggunakan RFID (Radio Frequency Identification) Berbasis Mikrokontroler Atmega16. Undip:SemarangWardani, dkk. 2008. Teknik Menulis Karya Ilmiah. Universitas Terbuka : JakartaWardhana, Lingga. 2006. Mikrokontroler AVR seri ATMEGA Simulasi, Hardware, dan Aplikasi. Andi : Yogyakarta